Hydrogels reinforced with nanoclays with improved response rate. Issue 9 (14th October 2016) - Djonlagic, Jasna; Lancuski, Anica; Nikolic, Marija S.; Rogan, Jelena; Ostojic, Sanja; Petrovic, Zoran
ABSTRACT: Two series of semiinterpenetrating networks (SIPN) based on linear hydrophilic poly(vinyl alcohol) (PVA) and thermo‐responsive poly( N ‐isopropylacrylamide) (PNIPA), physically crosslinked with inorganic clay, are presented. The hydrogels with different crosslinking densities were prepared by varying the content of clay from 1 to 6 wt % and contained linear interpenetrant, PVA in the range of 0.5–1.5 wt %. The effect of clay content on swelling/deswelling behavior and phase transition in PNIPA gels, as well as the feasibility of reinforcing the gels with high molecular weight PVA, were analyzed. The thermal response of hydrogels, followed by DSC, confirmed that the insertion of hydrophilic PVA did not have a significant effect on the onset of the volume phase transition temperature, while the response was faster. The equilibrium degree of swelling of SIPNs and PNIPA hydrogels was in the range of 9–79 and decreased with increasing content of clay. The internal morphology and surface wettability of the hydrogels were investigated by scanning electron microscope analysis and contact angle measurements, respectively. The network structural parameters of the PNIPA and SIPN nanocomposites hydrogels, such as the average molecular weight between crosslinks, M c, and effective crosslinking density, N e, were determined by dynamic mechanical analysis. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44535. Abstract :